2017
DOI: 10.1111/psj.12209
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Performance of Participatory and Collaborative Governance: A Framework of Causal Mechanisms

Abstract: Many have advocated for collaborative governance and the participation of citizens and stakeholders on the basis that it can improve the environmental outcomes of public decision making, as compared to traditional, top‐down decision making. Others, however, point to the potential negative effects of participation and collaboration on environmental outcomes. This article draws on several literatures to identify five clusters of causal mechanisms describing the relationship between participation and environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
232
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 291 publications
(238 citation statements)
references
References 89 publications
(254 reference statements)
4
232
0
2
Order By: Relevance
“…We specifically focus here on the role of participatory forums, which we take to represent organized and clearly articulated games where participation takes place, similar to “collaborative institutions” in the language of Lubell et al (). We borrow the definition given by Newig et al of participatory governance as “processes and structures of public decision making that engage actors from the private sector, civil society, and/or the public at large, with varying degrees of communication, collaboration and delegation of decision power to participants” (Newig, Challies, Jager, Kochskaemper, & Adzersen, , p. 5). We similarly prefer the term participation to collaboration, as collaboration more aptly describes one of the possible forms of interaction within participatory forums.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…We specifically focus here on the role of participatory forums, which we take to represent organized and clearly articulated games where participation takes place, similar to “collaborative institutions” in the language of Lubell et al (). We borrow the definition given by Newig et al of participatory governance as “processes and structures of public decision making that engage actors from the private sector, civil society, and/or the public at large, with varying degrees of communication, collaboration and delegation of decision power to participants” (Newig, Challies, Jager, Kochskaemper, & Adzersen, , p. 5). We similarly prefer the term participation to collaboration, as collaboration more aptly describes one of the possible forms of interaction within participatory forums.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…We similarly prefer the term participation to collaboration, as collaboration more aptly describes one of the possible forms of interaction within participatory forums. Most importantly, participation “stresses the involvement of actors who are not normally charged with decision making” (Newig et al, , p. 4). We do, however, acknowledge that the literature does not consistently follow this distinction and that the term collaboration might still be appropriate here, particularly as it conveys the presence of actors representing organized interests.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Many studies have analysed the performance of participatory processes in environmental policy and governance (e.g., Newig et al, 2017). However, literature exploring the presence and influence of different rationales in participatory practice is scarce.…”
Section: Critique Of Participation and Rationales In Practicementioning
confidence: 99%
“…There is a wealth of literature on the evaluation and performance of participation (e.g., Newig, Challies, Jager, Kochskämper, & Adzersen, 2017). However, the rationales for stakeholder participation-the underlying meanings attributed to participatory approaches-have rarely been explicitly explored in the CEE region, especially in the Baltic countries (Blicharska, Isaksson, Richardson, & Wu, 2011;Caddell, 2009;Wesselink, Paavola, Fritsch, & Renn, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Scott used quality data to test the relationship between collaborative governance and watershed quality, and found that a group engaging in management activities would be beneficial to greater environmental gains [23]. Newig et al identified five clusters of causal mechanisms describing the relationship between participation and environmental outcomes [24].…”
Section: Literature Reviewmentioning
confidence: 99%